Penerapan layanan konsultasi bagi Guru dalam menangani perilaku tantrum pada anak usia prasekolah - Harahap, Sartika Dara Alida; Sinaga, M. Harwansyah Putra (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Tantrum behavior in preschool children is a problem that is often faced by teachers in the educational environment. Tantrums can affect teaching and learning activities and overall student welfare. This study aims to explore the effectiveness of the implementation of counseling services for teachers in dealing with tantrums in preschool children. The purpose of this study is to assist teachers through consultation services in dealing with tantrum behavior in preschool children. The research design used in this study is